(untitled) (Burlington, MA, 2006)
The proposed book will look at serial predatory behavior and is comprised of two main parts. The first section deals with serial offenders by examining specific crime types (stalking, arson, murder, sexual assault, etc.) and proposing new paradigms for investigation based on psychological profiles, research, and cases studies of individuals involved in these cases. The second section deals with criminal profiling, one of the primary tools that aids in the investigative process aimed at narrowing down suspect pools. Profiling has typically seen most application in serial crimes and similar investigations, so the two topics are conceptually and practically related.
Keywords: Criminal behaviour, Prediction of.,Hoạt động hình sự, Dự báo